The Effect of Grape Temperature at Pressing on Phenolic Extraction and Evolution in Méthode Cap Classique Wines Throughout Winemaking - Mafata, M.; Buica, A.; du Toit, W.J.; van Jaarsveld, F.P. (South African Journal of Enology and Viticulture, 2018)
Phenolic compounds are important quality indicators of wine. Their composition in wine is determined by various factors, including grape variety, terroir, viticultural practices and oenological practices. There is very little extraction of colour compounds and, generally, very little phenolic content is expected and desired during traditional sparkling wine (TSW) vinification. Since phenolics are thought to reduce ageing capacity (Zoecklein, 2002), and are linked to browning in TSW (Ibern-Gómez et al., 2000), winemakers try to keep phenolic concentrations low throughout winemaking. This study investigated the effect of grape temperature at pressing on the phenolic extraction in Méthode Cap Classique (MCC) wines and the evolution of the phenolics throughout winemaking. MCC wines were made by the traditional method over two vintages (2014 and 2015) using Chardonnay and Pinot Noir grapes harvested from two regions (Robertson and Darling) and stored at 0°C, 10°C, 25°C and 30°C. MCCs made from grapes stored at lower temperatures (0°C and 10°C) were found to have lower total phenolic content, colour intensity and total hydroxycinnamates than wines made from grapes stored at higher temperatures (25°C and 30°C). This shows that there was greater phenolic extraction at higher temperatures. No changes in the phenolic content were observed throughout winemaking.